Attitude of Village Goverment To Use E-Village Budgeting (Evb) in Compilation of Add : An Integration of Decomposeed Theory Planned Behavior and Risk - M Iswahyudi; Rosidi Rosidi; Zaki Baridwan (e-2477-1929)
This study aims to examine the effect of perceived of ease of use, perceived usefulness, compatibility and perceived risk toward the attitude of e-Village Budgeting (EVB) system user. The use of the mandatory EVB system, as well as the obligation to use information systems in village budgeting, make research on user attitudes appealing to be researched. Data analysis using Partial Least Square (PLS) with warpPLS software version 3.0. The results showed that 1) Perceived Usefulness becomes the determinant factor of user attitude in using EVB system. 2) Perceived ease of use does not affect the attitude of users of EVB system. 3) Compatibility does not affect the attitude of users of EVB system and 4) Perceived risk does not affect the attitude of users of EVB system. This is because the perceived ease of use as a threshold variable and past users who previously used the manual budgeting system also affect the fit or not the EVB.